2006
DOI: 10.1016/j.ccr.2006.04.024
|View full text |Cite
|
Sign up to set email alerts
|

HMGA2 induces pituitary tumorigenesis by enhancing E2F1 activity

Abstract: HMGA2 gene amplification and overexpression in human prolactinomas and the development of pituitary adenomas in HMGA2 transgenic mice showed that HMGA2 plays a crucial role in pituitary tumorigenesis. We have explored the pRB/E2F1 pathway to investigate the mechanism by which HMGA2 acts. Here we show that HMGA2 interacts with pRB and induces E2F1 activity in mouse pituitary adenomas by displacing HDAC1 from the pRB/E2F1 complex-a process that results in E2F1 acetylation. We found that loss of E2F1 function (ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
222
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(235 citation statements)
references
References 23 publications
11
222
1
1
Order By: Relevance
“…For example, HMGA2 interacts with pRB to displace HDAC1, resulting in the enhanced activity of E2F1 (37). Our results herein propose an additional pathway, namely HMGA2-promoted PML protein degradation, underlying the oncogenic ability of HMGA2.…”
Section: Discussionmentioning
confidence: 63%
“…For example, HMGA2 interacts with pRB to displace HDAC1, resulting in the enhanced activity of E2F1 (37). Our results herein propose an additional pathway, namely HMGA2-promoted PML protein degradation, underlying the oncogenic ability of HMGA2.…”
Section: Discussionmentioning
confidence: 63%
“…By binding to AT-rich DNA and interacting with histone-modifying enzymes and other proteins in enhanceosomes and chromatin, Hmga2 functions as a global epigenetic regulator (22,23). Using a dissociated prostate regeneration approach (24), we examined the contribution of Hmga2-modified stroma to prostate cancer initiation and progression and found that overexpression of stromal Hmga2 was extraordinarily potent and led to the development of multifocal PIN in a paracrine Wnt-dependent manner.…”
Section: Significancementioning
confidence: 99%
“…All the other transfections were performed by using Lipofectamine 2000 (Invitrogen), as suggested by the manufacturer. The pCEFL-HA-HMGA1, pCEFL-HA-HMGA2, pCEFL-HA-HMGA1 (1-43) and pCEFL-HA-HMGA2 (1-73) vectors were previously described (Fedele et al, 2006;Pierantoni et al, 2001;Pentimalli et al, 2008). The anti-HMGA1 antisense construct was described elsewhere (Berlingieri et al, 2002).…”
Section: Chemicals and Treatmentsmentioning
confidence: 99%
“…Antibodies used were anti-FLAG M2 (Sigma, St Louis, MO, USA), anti-HA Clone 12CA5 (Roche, Branford, CT, USA), anti-P-ATM-substrate (phospho-Ser/Thr antibody), anti-CHK2pThr68 (Cell Signalling Technology, Danvers, MA, USA), anti-ATM S1981p (Rockland, Philadelphia, PA, USA), anti-p53 DO-1, anti-p-p53 (Ser15), anti-ATM and anti-vinculin (7F9) (Santa Cruz, Santa Cruz, CA, USA). Anti-HMGA1 and anti-HMGA2 polyclonal antibodies were described elsewhere (Pierantoni et al, 2001;Fedele et al, 2006).…”
Section: Chemicals and Treatmentsmentioning
confidence: 99%